Effects of Chronic Dopamine D2R Agonist Treatment and Polysialic Acid Depletion on Dendritic Spine Density and Excitatory Neurotransmission in the mPFC of Adult Rats - Esther Castillo-Gómez; Emilio Varea; José Miguel Blasco-Ibáñez; Carlos Crespo; Juan Nacher (Neural Plasticity)
Dopamine D2 receptors (D2R) in the medial prefrontal cortex (mPFC) are key players in the etiology and therapeutics of schizophrenia. The overactivation of these receptors contributes to mPFC dysfunction. Chronic treatment with D2R agonists modifies the expression of molecules implicated in neuronal structural plasticity, synaptic function, and inhibitory neurotransmission, which are also altered in schizophrenia. These changes are dependent on the expression of the polysialylated form of the neural cell adhesion molecule (PSA-NCAM), a plasticity-related molecule, but nothing is known about the effects of D2R and PSA-NCAM on excitatory neurotransmission and the structure of mPFC pyramidal neurons, two additional features affected in schizophrenia. To evaluate these parameters, we have chronically treated adult rats with PPHT (a D2R agonist) after enzymatic removal of PSA with Endo-N. Both treatments decreased spine density in apical dendrites of pyramidal neurons without affecting their inhibitory innervation. Endo-N also reduced the expression of vesicular glutamate transporter-1. These results indicate that D2R and PSA-NCAM are important players in the regulation of the structural plasticity of mPFC excitatory neurons. This is relevant to our understanding of the neurobiological basis of schizophrenia, in which structural alterations of pyramidal neurons and altered expression of D2R and PSA-NCAM have been found.